Diminished disease progression rate in a chronic kidney disease population following the replacement of dietary water source with quality drinking water: A pilot study. Issue 5 (25th April 2018) - Siriwardhana, Edirisinghe Arachchige Ranga Iroshanie Edirisinghe; Perera, Ponnamperuma Aratchige Jayasumana; Sivakanesan, Ramiah; Abeysekara, Tilak; Nugegoda, Danaseela Bandara; Weerakoon, Kosala; Siriwardhana, Dunusingha Asitha Surandika
Abstract: Aim: Environmental toxin/s is alleged to be the contributory factor for the chronic kidney disease of unknown aetiology (CKDu) in Sri Lanka. The potential of drinking water as a medium for the nephrotoxic agents in the affected subjects has been comprehensively discoursed in the recent past. The present study was aimed to assess the effect of replacing the habitual drinking water on the kidney function of CKDu patients residing in the North Central Province of Sri Lanka: Methods: An interventional study was carried out to assess the disease progression rate of a CKDu population whose habitual drinking water was replaced by bottled spring water certified by Sri Lanka Standard (SLS) for a period of 18 month along with a population of CKDu patients who continued with their usual drinking water. Kidney function of subjects in both groups were monitored in terms of blood pressure, serum creatinine, serum calcium, serum phosphorus, hemoglobin, estimated glomerular filtration rate and urinary protein at 6 months intervals during the intervention and follow up periods. Results: Diminished disease progression rate was observed in CKDu patients in the intervention group when compared with the non‐ intervention group based on serum creatinine, Hb, estimated glomerular filtration rate and urinary protein levels. Extensive interventional studies are required to generalize effect of drinking water on CKDu population. Conclusion: The habitual drinking water is likely to be a contributory factor towards the progression of the disease. Summary at a Glance: CKD of unknown cause is a growing problem in many parts of the world. This pilot study from Sri Lanka suggests that in their case, replacement of well water with bottled water for drinking, reduced the rate of renal failure ‐ thus prompting the likelihood of a contaminant in the drinking water as a factor in CKDu.